Selection of Temperature-Sensitive Mutants During Persistent Infection: Role in Maintenance of Persistent Newcastle Disease Virus Infections of L Cells - Preble, Olivia T. (J Virol, 1973)
Virus mutants (NDV(pi)) recovered from L cells persistently infected with Newcastle disease virus (NDV, Herts strain) are temperature-sensitive (ts) at 43 C, although the wild-type virus (NDV(o)) which initiated the persistent infection replicates normally at that temperature. To study the relationship between the ts marker of NDV(pi) and the other properties which distinguish this virus from NDV(o), NDV(pi) ts(+) revertants were selected at the nonpermissive temperature and NDV(o) ts mutants were generated by treating NDV(o) with nitrous acid. Spontaneously-occurring ts mutants in the Herts NDV population were also isolated. The different virus populations were characterized with regard to plaque size, virulence for eggs, and thermal stability of infectivity, hemagglutinin, and neuraminidase. The NDV(pi) ts(+) revertants, although no longer temperature-sensitive, retained NDV(pi) properties, whereas both spontaneously-occurring and mutagen-induced ts mutants remained wild-type in their other properties. These findings showed that the properties which characterized NDV(pi) were independent of the ts marker. However, the ts marker and the other markers of NDV(pi) were coselected during the persistent infection, and the combination of those markers appeared to be important in the outcome of NDV infection of L cells. NDV(pi) replicated productively in L cells, whereas NDV(o), the NDV(pi) ts(+) revertants, and the spontaneously-occurring ts mutants all yielded covert infections in L cells. The role of the selection of ts mutants in persistent infection was confirmed as follows: L cells were persistently infected with NDV(pi) ts(+) revertants and NDV(o) ts mutants. Virus recovered from the persistently infected cultures after eight cell passages was always temperature-sensitive and of smaller plaque size than the parental virus in chicken embryo cell cultures. Similar results were obtained with virus recovered from L-cell cultures persistently infected with two other velogenic strains of NDV, the Texas-GB and Kansas-Man strains. These results strongly suggest that selection of ts mutants during the persistent infection was not random and played a role in establishment or maintenance of the persistent infection, or both.